Comparing Indigenous and public health infant feeding recommendations in Peru: Opportunities for optimizing intercultural health policies - Monteban, Madalena (2018)
Background: The problem of childhood undernutrition in low-income countries persists despite long-standing efforts by local governmental and international development agencies. In order to address this problem, the Peruvian Ministry of Health has focused on improving access to primary healthcare and providing maternal and child health monitoring and education. Current maternal-child health policies in Peru introduce recommendations that are in some respect distinct from those of Indigenous highland communities. This paper analyses the similarities and differences between public health and mothers' infant feeding recommendations. Furthermore, it analyses persistence and change in those recommendations among women who were mothers before and after the introduction of current public health policies. Methods: Semi-structured interviews were conducted with 18 older mothers, 15 currently breastfeeding mothers, and 15 public health staff in highland rural communities of Peru. During data analysis, thematic codes and text passages were used in an iterative analytic process to document emerging themes. Results: The results highlight the existence of a traditional corpus of beliefs surrounding infant feeding and care that is consistent with Andean ethnomedical beliefs. This is illustrated by mother's accounts referring to the importance of maintaining a dietary balance of fluids and semi-fluids and of maintaining harmony with the elements in the natural environment. Mothers also incorporate aspects of public health recommendations that they find useful including initiating breastfeeding immediately after birth and exclusive breastfeeding up until 6months. There are also tensions between the two systems including differences in the conceptualization of breastfeeding and infant food, the imposition of public health care services by coercive means, and negative stereotyping of rural Andean diets and mothers. Conclusions: Identifying similarities and differences between distinct systems may provide useful input for effective intercultural health policies. Sources of tension should be carefully assessed with the aim of improving public health policies. Such efforts should apply a process of cultural humility engaging health care professionals in exchange and conversations with patients and communities acknowledging the assumptions and beliefs that are embedded in their own understanding. This process should also recognize and value the knowledge and practices of Andean mothers and their role as primary caretakers.